The enigma of the rise of angiosperms: can we untie the knot?. (29th June 2014) - Augusto, L.; Davies, T. J.; Delzon, S.; De Schrijver, A.; Chave, Jerome
Abstract Multiple hypotheses have been put forward to explain the rise of angiosperms to ecological dominance following the Cretaceous. A unified scheme incorporating all these theories appears to be an inextricable knot of relationships, processes and plant traits. Here, we revisit these hypotheses, categorising them within frameworks based on plant carbon economy, resistance to climatic stresses, nutrient economy, biotic interactions and diversification. We maintain that the enigma remains unresolved partly because our current state of knowledge is a result of the fragmentary nature of palaeodata. This lack of palaeodata limits our ability to draw firm conclusions. Nonetheless, based on consistent results, some inferences may be drawn. Our results indicate that a complex multidriver hypothesis may be more suitable than any single‐driver theory. We contend that plant carbon economy and diversification may have played an important role during the early stages of gymnosperms replacement by angiosperms in fertile tropical sites. Plant tolerance to climatic stresses, plant nutrition, biotic interactions and diversification may have played a role in later stages of angiosperm expansion within temperate and harsh environments. The angiosperm knot remains partly tied, but to unravel it entirely will only be feasible if new discoveries are made by scientific communities.